Methods for self-monitoring of daily salt and potassium intake at home - Tochikubo, Osamu; Sakon, Seiko; Osige, Kenji; Yamasue, Kotaro; Kono, Eiichi (Japanese Journal of Cardiovascular Disease Prevention, 2004)
For prevention and management of hypertension, decreasing salt intake and increasing potassium intake are very important. To attain this objective, there is a need to be able to measure daily salt and potassium intake easily at home. As most of these electrolytes are excreted in urine, we used overnight urine for 250 subjects. Regression analyses were performed to estimate 24-h urinary salt (NaCl24) and potassium (K24) from overnight (about 8 hour) urinary NaCl (NaCln) and potassium excretion (Kn) which was measured using an ion electrode method. The correlation coefficient between the NaCl24 and NaCln, K24 and Kn was 0.75 (p<0.001, n=250) and 0.71 (p<0.001, n=250) respectively. The formula of NaCl24=1.95NaCln +4.54 (g/day) and K24 =2.32Kn+1.03 (g/day) were derived. The new salimeter utilized in this study consists of a conductivity meter for measuring overnight urinary NaCl concentration, electrical resistance for measuring overnight urinary volume in a 1L urine cup, a central processor unit in which the above formula was installed and a display panel showing the predicted NaCl24 as a digital value. The correlation coefficient between the true NaCl24 and NaCl24 estimated by the new salimeter was 0.71 (n=159, p<0.001). The new salimeter could roughly estimate NaCl24 with ease and would be useful for self- monitoring of daily salt intake. Concentrations of NaCl and potassium of overnight urine were effectively measured using the compact salimeter C-121 and compact potassium ion meter (HORIBA) using a flat type ion electrode, although it was necessary to incorporate a correction formula when using undiluted urine.